Peningkatan Literasi Numerasi dan Keterampilan Kewirausahaan Dasar Melalui Pembelajaran Kontekstual Kewirausahaan - Pradana, Agrissto Bintang Aji; Wardana, Aditia Eska; Maharani, Betari (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service program was implemented at SD Negeri Bulurejo 1 to address the limited literacy and numeracy development of students with special needs (SSN) who often face barriers in conventional learning environments. The program adopted a multiple intelligence–based learning approach integrated with entrepreneurship-oriented practical activities, including oyster mushroom cultivation, vegetable hydroponics, salted egg production, and shoe cleaning services. The implementation was conducted through systematic stages consisting of needs assessment, development of adaptive learning modules and guidelines, training for teachers and parents, and intensive mentoring involving university students and school stakeholders. The evaluation results indicate a significant improvement in students’ learning outcomes. In the literacy domain, students’ achievement levels increased by one to two levels, progressing from predominantly levels 1–2 at the initial phase to 100% of students (18 participants) reaching level 3 at the final phase of the program. A similar pattern was observed in the numeracy domain, where all students (100%) demonstrated mastery of basic counting skills, simple addition and subtraction, and the application of numeracy in daily contexts. In terms of entrepreneurship skills, 40% of students showed measurable development in basic independence and responsibility during productive activities. Furthermore, teachers experienced improved competence in implementing inclusive, multiple intelligence–based instructional strategies, while parental involvement remained relatively low at 10%, indicating the need for further reinforcement. The program produced tangible outputs, including a community service article, posters, activity videos, press releases, and draft learning modules and implementation guidelines that support replication in other inclusive schools.